Living Place Matters: The Duplicity of Shared Housing in the Young Adults of South Korea - Byun, Nahyang; Shon, Donghwa (Frontiers in Psychology, 2022)
This study focus on the phenomenon of the preference for co-living among young adults that has manifested in South Korea. The study examines life in a shared house as a living place, which is the representative form of co-living that the younger adults in South Korea have been choosing. The objective of the study is to examine shared housing as living place matters and their possibility of being a home and house for the young generation. The study procedures included reviewing place attachment theory, analyzing the operational structure of share houses, and interviewing residents to discuss the place attachment of the residential environment in share houses. The young adult generation who chose to share a house display indecision on the issue of residential choices and behavior in terms of spatial possession. The results are as follows. Although co-living is a realistic residential choice for the reduction of residential costs, the majority of young adults experientially highlight the values of co-living rather than acknowledge the realistic reasons behind their choices. Such results signify that they recognize such limited residential choices as a means of temporary residence, not rooted to a living place, rather than an ordinal difference between the best and the second best, and ultimately the need to further consider the issues of continuous life and lifestyle on the foundation of the perspective of the universal life cycle of the young adult generation.